Open-Ended Approach as a Development of Imaginative Creativity in Learning History - Amanullah, Muhammad Abror; Putro, Rendy Wahyu Satriyo; Supriatna, Nana (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This study discusses Open-Ended questions by relying on questions that are stimulating and encourage students in learning history to imagine the question